PELATIHAN PENINGKATAN KINERJA UNTUK MEWUJUDKAN SISTEM PEMERINTAHAN YANG BAIK DI DESA MOJODELIK KECAMATAN GAYAM - Moh. Mustofa; Moehadi; Bima Permana Putra; Dimas Agung Sasmito (Jurnal Abdi Masyarakat, 2025)
Village apparatus performance improvement training is a strategic step in realizing a good governance system in Mojodelik Village, Gayam District. This program aims to improve the capacity of village apparatus in transparent, accountable, and effective governance. The main problems faced before mentoring include low understanding of the principles of Good Governance, weak village financial management, and less than optimal public services and community participation in village development. Mentoring is carried out through training, technical guidance, mentoring by experts, and periodic evaluations to ensure sustainable implementation. The results of the mentoring show significant improvements in aspects of administration, budget management, and more responsive and digital-based public services. In addition, village apparatus have become more professional in carrying out their duties, and the community has become more active in participating in village development planning. The implication of this program is the creation of a more transparent, efficient, and community-oriented village government system.